Anxiety about HIV criminalisation among people living with HIV in Australia. Issue 7 (3rd July 2022) - Bourne, Adam; Melendez-Torres, G. J.; Thanh Ly, An; Kidd, Paul; Cogle, Aaron; Brown, Graham; Lyons, Anthony; Carman, Marina; Rulee, John; Power, Jennifer
ABSTRACT: Many countries, including Australia, have laws that enable criminal prosecution of an individual based on reckless or intentional transmission of HIV to another person. Previous research has suggested that criminalisation of HIV may serve to hamper public health efforts by inhibiting HIV status disclosure or testing. Limited research to date has sought to examine the broader impact of criminalisation on the health and wellbeing of people living with HIV, which this paper aims to address. Drawing on cross-sectional data from 895 people living with HIV in Australia, this paper describes associations between standard measures of mental health and resilience with a newly devised scale measuring anxiety about HIV criminalisation. Findings suggest that laws criminalising HIV transmission have a broadly negative impact on wellbeing of people living with HIV, a situation that is exacerbated for gay and bisexual men, and other people living with HIV who may face intersecting forms of marginalisation based on race, gender or class. There is little justification for these laws being applied in Australia and the findings add weight to advocacy seeking to overturn criminalisation across the world.